A Case Report of Variance in the External Cord of the Brachial Plexus: The Absence of Musculocutaneous Nerve - Sara Azhdari; Motahareh Zaherara (Negah Institute for Scientific Communication, 2020)
The anatomical variations of the brachial plexus are well documented. However, it is important to review the components of the brachial plexus, as it is significant in everyday clinical practices. The lateral pectoral and musculocutaneous nerves emerge from the lateral side of the lateral cord, in the brachial plexus. Before the piercing of the coracobrachialis muscle, the cord gives a muscular branch to this muscle from its lateral side. After sending muscular branches to biceps brachii and brachialis, the cord pierces the coracobrachialis muscle. Then, it courses downwards for a long distance at the middle of the arm into the lateral forearm skin; this branch is named as lateral forearm cutaneous nerve. The variations of the musculocutaneous nerve are extremely important for surgeons and radiologists, especially in the surgical explorations involving this region. In this study, we reported the absence of musculocutaneous nerve on the left side of a 25-year-old male cadaver. The case was detected during the routine dissection of the upper limb, in the dissection hall of the Bam University of Medical Sciences. The left median nerve supplied the coracobrachialis, biceps brachii, and brachialis, thereafter, it gave way to the lateral forearm cutaneous nerve, close to the elbow joint. These branches crossed the brachial artery to supply the muscles. This absence of musculocutaneous nerve and such type of variations are very rare during the embryologic development. Thus, the awareness of such variations helps for the diagnosis of the related neurological disorders and in surgical procedures.